Generator of low pressure volume plasma with plasma electron source - Khomich, V.A.; Ryabtsev, A.V.; Nazarenko, V.G. (Вопросы атомной науки и техники, 2018)
In the current paper the results of a study of a volumetric high-current low-pressure discharge with a plasma
electron source are presented. The source was made on the basis of a hollow cathode with a gas-magnetron ignition
of the discharge and an auxiliary arc discharge for the cathode heating up to thermionic emission temperature. The
gas-discharge plasma was generated at a working gas pressure 0.1...1 Pa and hade an electron concentration of
10¹⁰ ...(5×10¹¹) cm⁻³
in a volume of 0.1 m³. Also the volt-ampere characteristics, the ion current density distribution
in the working volume are presented for different discharge conditions. The plasma generator may be used in the
processes of ion-plasma technologies (oxidation, nitration in non-hydrogen media), as well as in energy-saving
technologies of combined ion-plasma processing of structural materials. An improved electron plasma source with a
hollow cathode will allow one to work in a wide range of discharge currents and also will be served for a large
operating life of devices. Haведено результати дослідження об’ємного дугового розряду низького тиску з плазмовим джерелом
електронів, виконаним на основі порожнистого катода з газомагнетронним запалюванням розряду і
допоміжним дуговим розрядом для розігріву порожнистого катоду до термоемісійних температур.
Газорозрядна плазма, утворювана при тисках робочого газу 0,1…1 Па, має концентрацію електронів
10¹⁰ ...(5×10¹¹) см⁻³ в об’ємі 0,1 м³. Надано вольт-амперні характеристики та залежності розподілу густини
іонного струму в робочому об’ємі від умов розряду. Плазмогенератор може бути використаний в процесах
іоно-плазмових технологій (оксидування, азотування в безводневих середовищах), а також в
енергозберігаючих технологіях комбінованої іонно-плазмової обробки конструкційних матеріалів.
Вдосконалене плазмове джерело електронів з порожнистим катодом дозволить працювати в широкому
діапазоні розрядних струмів і з більшим робочим ресурсом пристрою. Приведены результаты исследования объемного сильноточного разряда низкого давления с плазменным
источником электронов, выполненным на основе полого катода с газомагнетронным зажиганием разряда и
вспомогательным дуговым разрядом для разогрева катода до термоэмиссионных температур. Газоразрядная
плазма, генерируемая при давлении рабочего газа 0,1…1 Па, имеет концентрацию электронов
10¹⁰ ...(5×10¹¹) см⁻³ в объеме 0,1 м³. Представлены вольт-амперные характеристики, зависимости
распределения плотности ионного тока в рабочем объеме от условий разряда. Плазмогенератор может быть
использован в процессах ионно-плазменных технологий (оксидирования, азотирования в безводородных
средах), a также в энергосберегающих технологиях комбинированной ионно-плазменной обработки
конструкционных материалов. Усовершенствованный плазменный источник электронов с полым катодом
позволит работать в широком диапазоне разрядных токов и с большим рабочим ресурсом устройства.